14‐3‐3epsilon controls multiple developmental processes in the mouse heart. Issue 11 (18th September 2016) - Gittenberger‐de Groot, Adriana C.; Hoppenbrouwers, Tamara; Miquerol, Lucile; Kosaka, Yasuhiro; Poelmann, Robert E.; Wisse, Lambertus J.; Yost, H. Joseph; Jongbloed, Monique R.M.; Deruiter, Marco C.; Brunelli, Luca
Abstract : Background: 14‐3‐3ε plays an important role in the maturation of the compact ventricular myocardium by modulating the cardiomyocyte cell cycle via p27 kip1 . However, additional cardiac defects are possible given the ubiquitous expression pattern of this protein. Results: Germ line deletion of 14‐3‐3ε led to malalignment of both the outflow tract (OFT) and atrioventricular (AV) cushions, with resulting tricuspid stenosis and atresia, mitral valve abnormalities, and perimembranous ventricular septal defects (VSDs). We confirmed myocardial non‐compaction and detected a spongy septum with muscular VSDs and blebbing of the epicardium. These defects were associated with abnormal patterning of p27 kip1 expression in the subendocardial and possibly the epicardial cell populations. In addition to abnormal pharyngeal arch artery patterning, we found deep endocardial recesses and paucity of intramyocardial coronary vasculature as a result of defective coronary plexus remodeling. Conclusions: The malalignment of both endocardial cushions provides a new explanation for tricuspid and mitral valve defects, while myocardial non‐compaction provides the basis for the abnormal coronary vasculature patterning. These abnormalities might arise from p27 kip1 dysregulation and a resulting defect in epithelial‐to‐mesenchymal transformation. These data suggest that 14‐3‐3ε, in addition to left ventricular non‐compaction (LVNC), might be linked to different forms of congenital heart disease (CHD). Developmental Dynamics 245:1107–1123, 2016 . © 2016 Wiley Periodicals, Inc. Key Findings: Germ line deletion of 14‐3‐3ε in the mouse leads to a very high incidence of multiple cardiac malformations. Malalignment of both the outflow tract (OFT) and the atrioventricular (AV) endocardial cushions, leading to tricuspid stenosis/atresia and mitral valve abnormalities. In addition to muscular VSDs and myocardial non‐compaction, we identified epicardial blebbing and deep endocardial recesses. Abnormal pharyngeal arch artery patterning and defects in coronary vasculature remodeling. Abnormal patterning of p27 kip1 in the endocardium might trigger some of the described developmental malformations through the disturbance of epithelial‐to‐mesenchymal transformation.